2009
DOI: 10.1002/elps.200800402
|View full text |Cite
|
Sign up to set email alerts
|

The combination of flow injection with electrophoresis using capillaries and chips

Abstract: The technique of combined flow injection CE (FI-CE) integrates the essential favorable merits of FI and CE. It utilizes the various excellent on-line sample pretreatments and preconcentration (such as cloud point extraction, SPE, ion-exchange, dynamic pH junction and head-column field-amplified sample stacking technique) of FI, which has the advantages of high speed, accuracy, precision and avoiding manual handling of sample and reagents. Therefore, the coupling of FI-CE is an attractive technique; it can sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Conventional analytical methods to monitor the concentration of these acute toxic compounds include capillary electrophoresis [16], colorimetry [17], gas chromatography (GC) [18], mass spectrometry (MS) [19], thin layer chromatography [20, 21], and high performance liquid chromatography (HPLC) [22]. The above said methods have some limitations, that is, sample preparation which is hectic and time consuming; requiring expensive equipments and trained manpower; less economical; and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional analytical methods to monitor the concentration of these acute toxic compounds include capillary electrophoresis [16], colorimetry [17], gas chromatography (GC) [18], mass spectrometry (MS) [19], thin layer chromatography [20, 21], and high performance liquid chromatography (HPLC) [22]. The above said methods have some limitations, that is, sample preparation which is hectic and time consuming; requiring expensive equipments and trained manpower; less economical; and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…It is principally based on shortening separation pathways to be applied both in commercial and specialized, portable CE instrumentation. Technical innovations for interfacing CE with flow and sequential injection analysis (SIA) as sampling means have been addressed in three complementary review papers 8–10. Updated insights into separation modes that are generally less common for inorganic analytes, such as MEKC 11, MEEKC 12, NACE 13, CEC 14, or based on using ionic liquids as BGE additives 15, 16, revealed that these are still limited to solve selectivity (and solubility) issues.…”
Section: Reviewsmentioning
confidence: 99%
“…It was preceded by the success of segmented flow analysis, mainly in clinical and environmental analysis. This advance, as well as the development of continuous monitors for process control and environmental monitors, ensured the success of the FIA methodology (Trojanowicz et al, 2009;Lü et al, 2009). A combination of CE with a flow injection (FI) offers a great scale of sample preparation and the most frequently it is used for the on-line implementation of chemical reactions.…”
Section: Fi-cementioning
confidence: 99%